ISLAMIC ETHICS IN SOCIAL MEDIA - Lisnawati Lisnawati; Desi Erawati (IAIN Tulungagung, 2019)
This article addresses social media, family life and its intersection with Islamic ethics. It particularly discusses the use of social media to protect harmony of family life as to which communication ethics on social media for married-couples to prevent family disharmony. A close look at sources ranging from Islamic sources, magazines, newspapers, official documents of the local religious court (Pengadilan Agama), this article argues that there are seven communication ethics through social media crucial to prevent disharmony. These seven are to take benefits and to leave losses, meaning that social media has benefits if used wisely; to practice fair time management; to be open with your partner; to select friends wisely; to say corresponding statement in posts and comments; to keep the couple’s disgrace and not to indulge themselves on social media; and to look after self-esteem.